2013
DOI: 10.1007/s10897-013-9605-3
|View full text |Cite
|
Sign up to set email alerts
|

What's the Harm? Genetic Counselor Perceptions of Adverse Effects of Genetics Service Provision by Non‐Genetics Professionals

Abstract: Anecdotal accounts suggest some patients have experienced negative outcomes as a result of receiving genetics services from non-genetics providers, but empirical evidence of these incidents and their outcomes is limited. This study examined genetic counselors' perceptions of the occurrence of such incidents in the state of Minnesota. Twenty-five genetic counselors completed an on-line survey and 20 also participated in a semi-structured telephone interview. The interviewees recalled and described 37 specific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 22 publications
6
76
0
Order By: Relevance
“…[13][14][15][16][17][18][19] The Veterans Health Administration (VHA) is the largest integrated health-care system in the United States, serving more than 8.3 million Veterans at 153 Veterans Affairs Medical Centers (VAMCs). 20 The VAMCs are located within 21 Veterans Integrated Service Networks (VISNs) nationwide.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] The Veterans Health Administration (VHA) is the largest integrated health-care system in the United States, serving more than 8.3 million Veterans at 153 Veterans Affairs Medical Centers (VAMCs). 20 The VAMCs are located within 21 Veterans Integrated Service Networks (VISNs) nationwide.…”
Section: Resultsmentioning
confidence: 99%
“…13 Our telegenetics application was an example of interactive telemedicine, substituting the setting of care by introducing online genetic counseling at patients' homes instead of counseling at the OPD of our university center, with the same genetic professionals and content of care as in conventional genetic counseling, as current professional guidelines and the professionals' view recommend. 14,15 The results showed that our application was feasible that patients were satisfied with the online counseling, with its efficiency, and with the specific online application we used. Levels of anxiety and personal perceived control of online patients and controls were comparable, thereby demonstrating equivalence of online counseling and regular OPD counseling from the patients' perspective.…”
Section: Introductionmentioning
confidence: 90%
“…2 In addition, there is research demonstrating patient harm in the absence of high-quality genetic services accompanying genetic testing. [3][4][5][6] However, perception of limited access to and availability of cancer genetic counseling services by a board-eligible or board-certified genetic counselor (GC) has the potential to form an unnecessary barrier to comprehensive genetic risk assessment, counseling, and testing. In this report we outline the current state of access to genetic counseling, including evidence from a recent survey of GCs focused on wait time for urgent consultations.…”
Section: Brief Report © American College Of Medical Genetics and Genomentioning
confidence: 99%